New Old Forms: Djuna Barnes’s and Virginia Woolf’s Return to the Archaic as Experimental Modernist Form - Elaine Hsieh Chou (Angles)
The following paper posits that High Modernism regards experimental literature purely in terms of form, not content; and how this regard is rooted in the gendering of literature i.e. masculine signaling “experimental” and feminine signaling “traditional.” As a result, the modernist canon is rooted in the exclusion of the other, notably texts that disrupt conservative views on gender and sexuality. I show how, contrary to popular belief, Djuna Barnes’s Ladies Almanack and Virginia Woolf’s Orlando are two experimental modernist texts, both in terms of their “archaic” language and in terms of their sexual politics. The fact that both texts are indeed experimental forces Modernism to reexamine its exclusionary practices and how it defines experimentalism.